Review paper Indication for percutaneous aortic valve implantation - Akin, Ibrahim; Kische, Stephan; Rehders, Tim C.; Nienaber, Christoph A.; Rauchhaus, Mathias; Ince, Hüseyin; Schneider, Henrik; Liebold, Andreas (Archives of Medical Science, 2010)
The incidence of valvular aortic stenosis has increased over the past decades due to improved life expectancy. Surgical aortic valve replacement is currently the only treatment option for severe symptomatic aortic stenosis that has been shown to improve survival. However, up to one third of patients who require lifesaving surgical aortic valve replacement are denied surgery due to high comorbidities resulting in a higher operative mortality rate. In the past such patients could only be treated with medical therapy or percutaneous aortic valvuloplasty, neither of which has been shown to improve mortality. With advances in interventional cardiology, transcatheter methods have been developed for aortic valve replacement with the goal of offering a therapeutic solution for patients who are unfit for surgical therapy. Currently there are two catheter-based treatment systems in clinical application (the Edwards SAPIEN aortic valve and the CoreValve ReValving System), utilizing either a balloon-expandable or a self-expanding stent platform, respectively.